Validity of a Self-Reported Neglect Scale Among Older Adults in Poland. (15th March 2019) - Zawisza, Katarzyna; Galas, Aleksander; Tobiasz-Adamczyk, Beata; Grodzicki, Tomasz
Abstract: Background and Objectives: The purpose of the study was to create and validate a tool that could be implemented easily to recognize the presence and assess the level of neglect in community-dwelling older adults, and to provide information about the prevalence of the phenomenon in different subgroups of older adults in Poland. Research Design and Methods: The cross-sectional study of elder neglect and self-neglect was conducted in Lesser Poland in 2017. It included 2, 443 face-to-face interviews with randomly selected community-dwelling individuals from among the general population (1, 635), social service users (280), and hospital patients (528). Classical Test Theory and Item Response Theory (IRT) were used to build the scale, and its content and construct validity and reliability were assessed. Results: The Self-Reported Neglect Scale (SRNS) with a 2-factor structure (basic needs and psychological needs dimensions) was created. Results of the IRT analysis showed high item discrimination (2.7–4.8 for the first factor, 0.8–3.2 for the second). The 1-year prevalence of neglect as a percentage of nonzero values of the SRNS was estimated at 11.4%. Discussion and Implications: The SRNS exhibited good psychometric properties. It may have promise as a tool for the assessment of neglect in epidemiological studies as well in the everyday practice of medical professionals and social workers.